A Follower-Centric Approach to Leadership in the Newsroom: The case of El País. (21st April 2018) - Goyanes, Manuel; Gentile, Alessandro
Abstract : This article analyses leadership in the newsroom of the Spanish newspaper El País as well as its impact on the craft of journalism more generally. Through 23 in-depth interviews, we try to elucidate how the newsroom constructs its leaders (in the newsroom, what does it mean to be a leader?), paying particular attention to the main skills considered to be necessary. According to our newsroom findings, not all heads of section or editors-in-chief are leaders, a fact that questions formal authority relations and proclaims expertise and know-how as discriminatory skills. This study emphasizes that the collective recognition of a leader is not an ultimate disposition, but can vary over time: consequently leaders who do not achieve the professional requirements of the newsroom can be denied the status, despite their expertise and experience. Our findings indicate that leaders at El País are those journalists (no matter what their positions) with strong capacities and skills (fundamentally experience, expertise and creativity) to manage form (relationships) and substance (contents) in the daily work of the newsroom. In short, journalists seen as leaders combine reiterated and strong qualities and merit, graphically reflected in the texts they have published for years in the newspaper.